2021
DOI: 10.1038/s41467-021-22010-9
|View full text |Cite
|
Sign up to set email alerts
|

Apico-basal cell compression regulates Lamin A/C levels in epithelial tissues

Abstract: The levels of nuclear protein Lamin A/C are crucial for nuclear mechanotransduction. Lamin A/C levels are known to scale with tissue stiffness and extracellular matrix levels in mesenchymal tissues. But in epithelial tissues, where cells lack a strong interaction with the extracellular matrix, it is unclear how Lamin A/C is regulated. Here, we show in epithelial tissues that Lamin A/C levels scale with apico-basal cell compression, independent of tissue stiffness. Using genetic perturbations in Drosophila epit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Apart from nuclear YAP translocation, forces applied to the nucleus can trigger different mechanotransduction events, which could also take place in our system. For instance, Lamin A/C levels have been shown to affect nuclear mechanics and nuclear shape integrity 72,73 , and nuclear deformation regulates Lamin A/C levels 74 . We found no significant difference between WT and β4R1281W cells in the overall expression levels of lamin A/C, indicating that the nuclear lamina was not compromised (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from nuclear YAP translocation, forces applied to the nucleus can trigger different mechanotransduction events, which could also take place in our system. For instance, Lamin A/C levels have been shown to affect nuclear mechanics and nuclear shape integrity 72,73 , and nuclear deformation regulates Lamin A/C levels 74 . We found no significant difference between WT and β4R1281W cells in the overall expression levels of lamin A/C, indicating that the nuclear lamina was not compromised (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In mammals, the levels of Lamin A/C rise with increasing tissue stiffness and these form a meshwork in the nuclear lamina distinct from that formed by Lamin B filaments that increases the stiffness of the nuclear envelope, thereby protecting it from mechanical deformation (Lammerding et al, 2006;Swift et al, 2013). It has recently been found that Lamin C expression in Drosophila epithelia shows a similar correlation with apical compression (Iyer et al, 2021). Both the peripodial membrane and the folds of the wing disc are under compression and have high Lamin C levels, whereas the wing pouch epithelium, which is not compressed, has low levels.…”
Section: Journal Of Cell Science • Accepted Manuscriptmentioning
confidence: 99%
“…Namely, from the results published in ref. [25,117], it follows that the cell shape and/or mechanical properties of the surround-ing environment have a profound effect on the expression level of lamin A, which, in turn, has a strong influence on the elastic properties of the nuclear lamina network and therefore the surface tension of the NE [47]. The latter, according to our study, determines the nucleus size and, as a result, nucleosome stability, which may have a global impact on gene transcription profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, based on recent experimental studies it has been suggested that by modulating DNA-binding properties of architectural proteins, cells may be able to actively respond to a wide range of environmental cues via changing the condensation level of various parts of DNA and switching between different gene expression patterns [12][13][14][15][16][17][18]. Furthermore, it has been found that such a mechanism not only plays the central role in cell response to chemical signals [12][13][14], but also to extracellular mechanical forces as well [16][17][18][19][20][21][22][23][24][25]. In the latter case, rearrangement of the chromatin structure and changes in gene transcription have been found to be tightly associated with alternations in the nucleus size and shape [18,21,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation